2002
DOI: 10.1038/sj.bmt.1703716
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, taste, olfactory and oral function following high-dose chemotherapy and allogeneic hematopoietic cell transplantation

Abstract: Summary:Multiple oral complaints develop following high-dose chemo/radiotherapy and hematopoietic cell transplantation (HCT) which can influence quality of life. The purpose of this investigation was to assess quality of life, oral function, taste and smell in a cohort of patients following HCT. A general quality of life survey (the European Organization for Research and Treatment of Cancer (EORTC)) Quality of Life (QOL) questionnaire (QLQ-C30), with an added oral symptom and function scale and assessment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 30 publications
3
75
0
10
Order By: Relevance
“…Previous studies have had mixed findings regarding the association between gender and chemosensory alterations, with some studies finding no gender differences (14) and others finding females more likely than males to experience sensitivities (26). In this study, females were more likely than males to report some chemosensory alterations.…”
Section: Discussionmentioning
confidence: 33%
“…Previous studies have had mixed findings regarding the association between gender and chemosensory alterations, with some studies finding no gender differences (14) and others finding females more likely than males to experience sensitivities (26). In this study, females were more likely than males to report some chemosensory alterations.…”
Section: Discussionmentioning
confidence: 33%
“…Our results are in accordance with the results of Ovesen et al, who also failed to demonstrate impaired olfaction following treatment with cisplatin. A quality-of-life questionnaire-based study reported a subjective change in sense of smell in 26% of patients following high-dose chemotherapy and bone marrow transplantation, although more patients reported an increase in smell sensation rather than a decrease (Epstein et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1 It can induce severe pain, prevent oral intake, result in airway obstruction, increase the risk of infection and possibly initiate or exacerbate acute gastrointestinal GVHD. [2][3] Factors predisposing to severe mucositis include TBI containing regimens, recipients with a high body mass index and the presence of the methylenetetrahydrofolate reductase 677 TT genotype. [4][5] Fractionated TBI and high-dose etoposide (FTBI-VP16) conditioning has been reported to prolong disease-free survival in comparison to CY and TBI (CYTBI) in patients with ALL beyond first CR.…”
Section: Introductionmentioning
confidence: 99%